Jejak-Jejak Tertulis: Sejarah Pembukuan Hadis Dalam Islam - Akbar Waliyuddin Pakpahan; Mutohharun Jinan (Tanjak: Sejarah dan Peradaban Islam, 2024)
This study examines the development, controversy, and influence of hadith bookkeeping in the Islamic tradition from early times to modern contexts. Hadith, as the second source in the Islamic religious hierarchy after the Quran, played an important role in directing religious practice, the establishment of Islamic law, and understanding of the teachings of the Prophet Muhammad (PBUH) as well as the early period of Islam. Although it began soon after the death of the Prophet, the process of bookkeeping hadith has been marred by controversies surrounding authority, reliability, and methodology. These controversies include the validity of hadiths, the reliability of narrators, selection criteria, and methodologies of interpretation, as well as political and ideological influences in the bookkeeping process. Through a qualitative approach with literature studies, this study analyzes patterns, themes, and arguments that arise in literature related to history, methodology, and controversy in hadith bookkeeping. The results showed that hadith bookkeeping had a significant role in the development of Islamic thought and practice, despite methodological debates. Hadith bookkeeping remains an important cornerstone in the Islamic tradition, and the advice for the future is to maintain the quality and integrity of the hadith bookkeeping process and pay attention to various perspectives in interpreting and applying hadith in a contemporary context.